Kinematics and workspace analysis of a robotic arm for medical delivery robots - Wang Wenli; Wang Peng; Zhao Yongguo; Zhu Yunhai; Zhao Jie (E3S Web of Conferences, 2021)
For the control of the robot arm of a medical delivery robot, firstly, the forward kinematic equations of this 7-degree-of-freedom redundant robot arm are constructed according to a modified D-H method. Secondly, the analytical solution of the inverse kinematics of the redundant robotic arm is solved using the parameterised arm angle. Thirdly, kinematic simulation experiments were carried out by gazebo and RVIZ in ROS to verify the correctness of the forward and inverse kinematic solution process. Finally, the Monte Carlo method was used to generate the point cloud map of the workspace of the redundant robotic arm within the allowed range of joints, and the boundary points of the workspace were extracted, and the extracted boundary points were fitted with least squares curves to find the workspace of the robotic arm, which laid the foundation for future research directions such as motion control and path planning of medical delivery robots.